VISUALISASI GLOBAL WARMING UNTUK SD DENGAN ADOBE FLASH CS - Rohmawati; Rizka Safitri Lutfiyani; Mariana Windarti (Journal of Computer Science and Technology, 2021)
One of the obstacles of elementary school learning process is there of material that cannot be directly observed by students. Childrens quickly get bored and not focus on materials like that. Science is one of the subject that has a lot of material that cannot be directly observed, example a global warning. Through learning media with visualization, it be expected that the material can be delivered well. There are four stages of this research, that is data requirenment, design, implementation and testing. The techniques used at the data requirenment stage are interviews and observations. Meanwhile, at the design stage, storyboards and other designs of this learning media were made. In the third stage, the previously created design is implemented by the Adobe Flash CS3 application. The final stage, the results of the design are examined by means of a questionnaire. The result of this research is a learning media made with lots of visuals so that students stay focused on the material. The suggestion of this research is that this research can be developed using a smartphone, android.